Pulmonary function and functional capacity of illicit drug users in detoxification process - Palú, Marina; Santos, Karoliny dos; Scalco, Janaína Cristina; Cani, Katerine Cristhine; Santos, Jefferson Jovelino Amaral dos (Medicina (Ribeirao Preto), 2016)
Importance of the problem: The use of psychoactive substances represents a public health problem, causing complications that go beyond the social. Aim: Investigate the pulmonary function and functional capacity of drug addicts admitted to a rehabilitation center. Methods: Case reports with 13 men (24 ± 2.9 years), drug users and abstinence time of up to nine months, perform a protocol consisting of sociodemographic interview, spirometry and six minute walk test. Results: In the six-minute walk test, traveled on average 129% of the scheduled distance and pulmonary function showed no impairment. The majority began substance use in adolescence; in addition, presented the combined substance use and family history of consumption of psychoactive substances and alcohol. Comments: The findings suggest that the use of illegal drugs for less in twenty years does not alter pulmonary function and functional capacity